If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 9 = 9x + 27 Reorder the terms: 9 + 12x = 9x + 27 Reorder the terms: 9 + 12x = 27 + 9x Solving 9 + 12x = 27 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 9 + 12x + -9x = 27 + 9x + -9x Combine like terms: 12x + -9x = 3x 9 + 3x = 27 + 9x + -9x Combine like terms: 9x + -9x = 0 9 + 3x = 27 + 0 9 + 3x = 27 Add '-9' to each side of the equation. 9 + -9 + 3x = 27 + -9 Combine like terms: 9 + -9 = 0 0 + 3x = 27 + -9 3x = 27 + -9 Combine like terms: 27 + -9 = 18 3x = 18 Divide each side by '3'. x = 6 Simplifying x = 6
| 4x^2-32x+50= | | y+4=-15 | | ax+7=5 | | 63-2x=34x+23 | | 6-9x=110-37x | | 5x+12=-33-10x | | 102-5x=2x+18 | | 138-3x=33x+22 | | 9-10x=20-17x | | 2-6x=14-9x | | 5x+11=-17-9x | | 134-6x=4x+14 | | -30-3x=10-3x | | 4x+26=14x-74 | | 5x+28=7x+12 | | 8x+8=6x+22 | | Y=11+6x | | 12x+7=6x+43 | | v+0.5=7.25 | | 1=8n-7 | | 7t+5=68 | | 15g-9=51 | | 8b+4=36 | | 6.4=4u | | 3-12m=15-8m | | 2x^3+5x^2-7x-30=0 | | y=4+3x | | 263n+441n=714n | | 2x(2-1)=3x | | -12a+10+11a=30 | | 3v+4=6v+19 | | 8w-5=3w+1 |